1993
DOI: 10.1007/bf00925693
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA for epidermal growth factor, transforming growth factor-alpha and their receptor in human prostate tissue and cell lines

Abstract: Enhanced expression of the epidermal growth factor receptor (EGFR) or its ligands, epidermal growth factor (EGF) and transforming growth factor alpha (TGF-alpha) can increase signalling via receptor-mediated pathways which may lead to excessive proliferation and cellular transformation. Such autocrine regulation of growth has been demonstrated for prostate cancer cell lines in culture but its role in prostate cancer in vivo has not been established. To assess the potential of such a mechanism, we have examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
59
0
4

Year Published

1996
1996
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 32 publications
6
59
0
4
Order By: Relevance
“…Moreover, recent data indicate that chimeric monoclonal EGFR antibodies can significantly inhibit the growth of DU145 and PC3 cell xenografts in nude mice (Prewett et al, 1997). Analysis of the responses to EGF and TGF-α in the androgen-independent DU145 and PC3 cell lines which overexpress EGFRs suggests that part of the progression to hormone-independence involves a 'switch' in secretion from EGF to TGF-α (Ching et al, 1993), and development of an autocrine loop. Evidence supporting the existence of an autocrine loop involving TGF-α and the EGFR has been obtained in prostate carcinoma specimens (Glynne-Jones et al, 1996), as well as in prostate cancer cell lines (Ching et al, 1993;Liu et al, 1993).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, recent data indicate that chimeric monoclonal EGFR antibodies can significantly inhibit the growth of DU145 and PC3 cell xenografts in nude mice (Prewett et al, 1997). Analysis of the responses to EGF and TGF-α in the androgen-independent DU145 and PC3 cell lines which overexpress EGFRs suggests that part of the progression to hormone-independence involves a 'switch' in secretion from EGF to TGF-α (Ching et al, 1993), and development of an autocrine loop. Evidence supporting the existence of an autocrine loop involving TGF-α and the EGFR has been obtained in prostate carcinoma specimens (Glynne-Jones et al, 1996), as well as in prostate cancer cell lines (Ching et al, 1993;Liu et al, 1993).…”
mentioning
confidence: 99%
“…The epidermal growth factor receptor (EGFR) and two of its multiple high affinity ligands, EGF and TGF-α, play an important role in the development of several different human cancers (Todaro et al, 1979;Lippman, 1993), including prostate cancer (Ching et al, 1993). Several studies have shown that prostate cancer cells express EGF, TGF-α and EGFR mRNA and protein (Morris and Dodd, 1990;Ching et al, 1993;Glynne-Jones et al, 1996).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been suggested that the progression to the androgen-independent state may involve a switch in the predominant ligand from EGF to TGF-a. 124 In vitro studies using the DU145 cell line have shown that EGFR-mediated signals enhance cell transmigration of an extracellular matrix. This increased invasiveness has been shown to be independent of proteolytic degradation of the matrix 125 and not due to altered growth.…”
Section: Egf and Tgf-amentioning
confidence: 99%